Original papersLidocaine bolus may facilitate computed tomographic coronary angiography in patients with frequent premature ventricular contractions - Pręgowski, Jerzy; Jastrzębski, Jan; Kępka, Cezary; Kruk, Mariusz; Demkow, Marcin; Kalińczuk, Łukasz; Wolny, Rafał; Ciszewski, Michał; Michałowska, Ilona; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction: Heart rate irregularities are the major limitations of computed tomographic coronary angiography (CTCA) due to severe motion artifacts. Aim: To evaluate the safety and efficacy of a lidocaine intravenous bolus in preserving good image quality by the transient suppression of premature ventricular contractions (PVC) during the CTCA scan. Material and methods: The study group comprised 67 consecutive patients with sinus rhythm and numerous PVC scheduled for CTCA. Intravenous boluses of 25–50 mg lidocaine were given after calcium score assessment and immediately before CTCA. The control group comprised 67 patients with sinus rhythm without PVC matched according to the body mass index (BMI), age, sex, and calcium score. All coronary vessel segments were assessed for image quality and presence of significant stenosis. Results: As compared with calcium score assessment, after administration of lidocaine and during the CTCA scan PVC were completely suppressed in 22 (40%), reduced in 10 (18%), unchanged in 18 (32%), and intensified in 5 (10%) patients. Overall, there were 32 (58%) patients with sinus rhythm during CTCA as compared with only 11 (20%) patients free from PVC during calcium score assessment (p < 0.001). Image quality in 871 coronary segments including both the study group and control patients was worse in patients with PVC (p < 0.0001). However, there was no statistically significant difference in the number of patients with at least one segment of non-diagnostic quality (6% vs. 12%, p = 0.36; respectively). Conclusions : Single lidocaine bolus given prior to CTCA is safe, may temporarily eliminate or reduce the intensity of arrhythmia, and hence results in improved quality of CTCA in patients with numerous PVC.